2017
DOI: 10.2217/nnm-2017-0126
|View full text |Cite|
|
Sign up to set email alerts
|

Lysosome-Dependent Necrosis Specifically Evoked in Cancer Cells by Gold Nanorods

Abstract: GNRs can specifically trigger lysosome-dependent necrosis in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Mild necrosis via DNA damage was induced by NIR-responsive GNRs (CTAB-stabilized) in A549 cells, while cell viability of normal human lymphocytes was not affected by the combined treatment of GNRs and NIR irradiation [ 80 ]. Furthermore, CTAB-capped GNR treatment disrupted lysosomes only in cancer cells, rather than normal cells, triggering both apoptosis and necrosis [ 81 ]. As mentioned above, there are still controversial reports on the cytotoxicity of CTAB-coated gold nanorods to cancer cells and normal cells, therefore, further investigation is still needed.…”
Section: Gnp-induced Necrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Mild necrosis via DNA damage was induced by NIR-responsive GNRs (CTAB-stabilized) in A549 cells, while cell viability of normal human lymphocytes was not affected by the combined treatment of GNRs and NIR irradiation [ 80 ]. Furthermore, CTAB-capped GNR treatment disrupted lysosomes only in cancer cells, rather than normal cells, triggering both apoptosis and necrosis [ 81 ]. As mentioned above, there are still controversial reports on the cytotoxicity of CTAB-coated gold nanorods to cancer cells and normal cells, therefore, further investigation is still needed.…”
Section: Gnp-induced Necrosismentioning
confidence: 99%
“…In cancer cells with decreased expression of intracellular glutathione (GSH), GNPs induced necrosis by elevating intracellular ROS [ 86 , 87 ]. In addition, the discovery of the GNR-induced necrosis mediated by the lysosomal-cathepsin B pathway provides a further understanding in the mechanisms of the GNR specific cytotoxicity against cancer cells [ 81 ].…”
Section: Gnp-induced Necrosismentioning
confidence: 99%
“…It is well established in the literature that most nanoparticles, when endocytosed by a cell, eventually primarily accumulate in the lysosomes. 15,[44][45][46][47][48][49][50][51] This is because the early endosomes, which contain the endocytosed material, are acidified and fuse with pre-lysosomal vesicles, before they turn into late endosomes and consequentially lysosomes. 52 A break-out of the nanoparticles from the endosomes on this pathway is unlikely unless endosomal escape strategies are employed.…”
Section: Plasmonic Photothermal Effect Of Non-targeted Ultrasmall Golmentioning
confidence: 99%
“…1 While inducing apoptosis has the advantage that no inflammatory response is triggered as the apoptotic vesicles are phagocytosed, it has also been suggested that this pathway could lead to development of resistances. 13 On the other hand necrosis is induced by inflicting substantial damage to key components of the cancerous cells such as the cell membrane or the mitochondria, 6,[13][14][15] which will inevitably lead to cell death. One of the downsides in the necrotic processes is that the cell is ultimately lysed completely and the cell fragments could lead to an inflammatory response in the organism.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the strategies of in-situ destruction of tumor tissue and enhancing the EPR may also lead to damage to normal cells and tissues with their associated undesired side effects. This indicates the importance of promoting intertumoral drug release without any in-vivo blood or non-tumor tissue damage through physical stimulation, such as using gold nanorods (GNRs) with a strong photothermal conversion effect (Zhang et al, 2016(Zhang et al, , 2017. In our previous studies, we found that the intratumoral drug accumulation was enhanced by temperature-sensitive passive targeting (TSPT) micelles composed of thermosensitive poly(Nisopropylacrylamide) (PNIPAM) (Li et al, 2011a(Li et al, , 2012d.…”
Section: Introductionmentioning
confidence: 99%